Factors that contribute in student's dependency on smartphones among degree students of UiTM Sabah / Mohd Haliff Nasir - Nasir, Mohd Haliff (2014)
The purpose of this research is to study the factor that contributes in students' dependency on smartphone. This research also examines the relationship between social needs, social influence and convenience towards students' dependency on smartphone. Thus, this investigation conducted among Universiti Teknologi Mara (UiTM) Sabah Cawangan Sabah degree students, whereas samples are chosen among 155 students who use smartphone. The research used certain method attain the result for the objective. Cronbach's Alpha reliability test is also used to measure the level of reliability of the research, while Multiple Regression analysis also used to analyze the data which is to show how strong the relationship between both variables and also to show its' significance. Findings of the results through multiple regression analysis revealed that social needs and convenience show its significant effect for the study while social influence show negative relationship with the dependency on smartphone. Convenience results in to have the strongest effect towards the dependency on smartphone. The results of this research are limited due to the unwillingness to contribute for the survey. In addition, this research might also have limitation due to the sample are restricted particularly on UiTM Sabah degree students only. Based on the findings from this research, the implication and future research of this research will be discussed in this paper.